ANALISIS PELAKSANAAN PERWAKO NOMOR 104 TAHUN 2020 TENTANG PEDOMAN HIDUP BARU MASYARAKAT DI RUMAH IBADAH (MASJID) KELURAHAN SIMPANG BARU KECAMATAN TAMPAN - Muhammad Tarmizi; Sri Erlinda; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is based on the background because there are still many people in Simpang Baru village, Tampan sub-district, who carry out worship, especially congregational prayer in mosques, do not comply with the health protocol in force. Such as not imposing distance in prayer shafts, wearing masks and there are still many people who do not wear masks when praying in mosques. The research aims to determine the implementation of Perwako Number 104 of 2020 concerning New Life Guidelines in Houses of Worship. The research was carried out in September 2020 until February 2021 at Simpang Baru Village, Tampan District, Pekanbaru City. In this study used qualitative methods and data collection techniques that researchers do is by observation, interview and documentation techniques. Determination of informants is done using. Incidental Sampling is a sampling technique based on chance, the informants chosen by the researcher were 20 worshipers and 5 mosque administrators from 5 mosques in Simpang Baru Village. Based on the results of the research conducted by the researchers, it can be seen that the implementation of Perwako Number 104 of 2020 concerning New Life Guidelines for Communities in Houses of Worship has been going well, but there are still mosques that have not implemented proper and perfect health protocols because of the opinion of congregations. who think if prayer does not close the shaf then the prayer feels imperfect even though there is a fatwa of Islamic religious scholars which allows prayer to keep a distance during the pandemic, but the congregation remains adamant about the stand that is in him and the understanding of religious knowledge that is embraced by the congregation in the mosque considers Islamic law to be rigid and standard. Key Words: Representative, House of worship.